The Influence of Understanding of Tamansiswa Teachings of Tri Abstinence and Religiosity on Tax Embezzlement Intentions of Prospective Taxpayers - Wardani, Dewi Kusuma; Setianingrum, Fransiska Agnes (Universitas Muhammadiyah Surakarta, 2023)
This study aims to examine the effect of understanding the teachings of tamansiswa on tri abstinence. Machiavellianism, love of money, the tax system, and religiosity on the intention to commit tax evasion by prospective taxpayers. This study used a quantitative descriptive method and primary data using a questionnaire. The number of samples in this study were 130 student respondents studying in Yogyakarta. Sampling in this study using snowball sampling technique. Data were analyzed using the IBM SPSS Statistic 20 program. This study provides the results of understanding the teachings of tamansiswa tri taboo which has a negative effect on the intention of tax evasion of prospective taxpayers. Machiavellian and love of money has a positive effect on tax evasion intentions of prospective taxpayers, the tax system and religiosity have no effect on intention of tax evasion prospective taxpayers.